2018
DOI: 10.4314/wsa.v44i3.08
|View full text |Cite
|
Sign up to set email alerts
|

Application of molecularly imprinted polymer designed for the selective extraction of ketoprofen from wastewater

Abstract: A molecularly imprinted polymer (MIP) that is selective to ketoprofen was synthesized and applied in the adsorption of the target compound from water. The MIP was synthesized using a bulk polymerization method at high temperatures (60–80°C), where ketoprofen, 2-vinylpyridine, ethylene glycol dimethacrylate, toluene and 1,1´-azobis(cyclohexanecarbonitrile) were used as template, functional monomer, cross-linker, porogen and initiator, respectively. Non-imprinted polymer (NIP) was synthesized similarly to the MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Therefore, always considering a more sustainable procedure for a cleaner production-pollution prevention, the use of 0.25 M NaCl was suggested for the DCF removal using 30 min as contact time for desorption. In this sense, the sea water could be used for this purpose, considering, as reported by Takagi et al [26], that the salt concentration in sea water was around 0.5 M. On this ground, several cycles of adsorption/desorption were performed and the percentage of the adsorbed/desorbed DCF, for each cycle, is reported in Figure 7. Once again, the desorbed DCF percentage is normalized with respect to the correspondent adsorbed DCF.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, always considering a more sustainable procedure for a cleaner production-pollution prevention, the use of 0.25 M NaCl was suggested for the DCF removal using 30 min as contact time for desorption. In this sense, the sea water could be used for this purpose, considering, as reported by Takagi et al [26], that the salt concentration in sea water was around 0.5 M. On this ground, several cycles of adsorption/desorption were performed and the percentage of the adsorbed/desorbed DCF, for each cycle, is reported in Figure 7. Once again, the desorbed DCF percentage is normalized with respect to the correspondent adsorbed DCF.…”
Section: Resultsmentioning
confidence: 98%
“…Kp is also frequently found in surface waters, which constitutes a potential risk for aquatic ecosystems [21,22,23,24]. Besides the studies reported in literature about its removal [25,26,27,28,29,30], the proposed use of CH to treat water from the Kp, according to our knowledge, has been not yet investigated. Therefore, regarding this aspect, to better emphasize the capacity of CH, preliminary results are discussed in this paper, which opens a novel possibility to treat water polluted with emerging pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…33 Relative selectivity indicates the magnitude of selectivity of the MIP in relation to the NIP, where values greater than one imply that the MIP is more selective to the analyte. 34 α = Q Analyte Q Analogue ð5Þ α = IF Analyte IF Analogue ð6Þ…”
Section: Commonly Applied Approaches In Determining the Success Ofmentioning
confidence: 99%
“…Nagy et al [25] reported the use of cyclodextrin-based polymers, working in synergy with filters, to exploit the possibility of working under dynamic conditions [25]. Madikizela et al [26] showed the efficiency of molecularly imprinted polymers, designed for the selective extraction of ketoprofen from wastewater [26].…”
Section: Introductionmentioning
confidence: 99%